Peningkatan Hasil Belajar Siswa pada pembelajaran PKn Mengunakan Model Pembelajaran Cooperative Learning Tipe Two Stay Two Stray Di Sekolah Dasar - HERDANI, HERDANI; Zuardi, Zuardi; Zuraida, Zuraida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The low learning outcomes of students in learning Civics in fourth grade students of SD Negeri 16 Campago Ipuh City Bukittinggi is caused by teacher-centered learning. The purpose of this study is to describe the improvement of learning outcomes in learning Civics by menngunakan cooperative learning model type two stay two stray in elementary school. This type of research is PTK by using qualitative and quantitative approach. Subject of this research is teacher and fourth grader of SDN 16 Campago Ipuh City Bukittinggi. The results of the research showed that in the first cycle the students' learning outcomes were 69.5% with sufficient qualification, increased in cycle II to 83% with good qualification. So it can be concluded that the use of Cooperative Learning Model Type Two Stay Two Stray in learning Civics can improve learning outcomes in fourth grade students of SD Negeri 16 Campago Ipuh City Bukittinggi.  Keywords: Learning Outcomes, Civics, Cooperative Learning Type Two Stay Two Stray.